Risk shifting elimination and risk sharing exposure in equity-based financing – a theoretical exposition - Hamzah S.R.; Ishak N.; Rasedee A.F.N. (Emerald Group Publishing Ltd., 2024)
Purpose: The purpose of this paper is to examine incentives for risk shifting in debt- and equity-based contracts based on the critiques of the similarities between sukuk and bonds. Design/methodology/approach: This paper uses a theoretical and mathematical model to investigate whether incentives for risk taking exist in: debt contracts; and equity contracts. Findings: Based on this theoretical model, it argues that risk shifting behaviour exists in debt contracts only because debt naturally gives rise to risk shifting behaviour when the transaction takes place. In contrast, equity contracts, by their very nature, involve sharing transactional risk and returns and are thus thought to make risk shifting behaviour undesirable. Nonetheless, previous researchers have found that equity-based financing also might carry risk shifting incentives. Even so, this paper argues that the amount of capital provided and the underlying assets must be considered, especially in the event of default. Through mathematical modelling, this element of equity financing can make risk shifting unattractive, thus making equity financing more distinct than debt financing. Research limitations/implications: Global awareness of the dangers of debt should be increased as a means of reducing the amount of debt outstanding globally. Although some regulators suggest that sukuk replaces debt, they must also be aware that imitative sukuk poses the same threat to efforts to avoid debt. In short, efforts to ensure future financial stability cannot address only debts or bonds but must also address those types of sukuk that mirrors bonds in their operation. In the wake of the global financial crisis, amid the frantic search for ways of protecting against future financial shocks, this analysis aims to help create future stability by encouraging market players to avoid debt-based activities and promoting equity-based instruments. Practical implications: This papers findings are relevant for countries that feature more than one type of financial market (e.g. Islamic and conventional) because risk shifting behaviour can degrade economic and financial stability. Originality/value: This paper differs from the previous literature in two important ways, viewing risk shifting behaviour not only in relation to debt or bonds but also when set against debt-based sukuk, which has been subjected to similar criticism. Indeed, to the extent that debts and bonds encourage risk shifting behaviour and threaten the entire financial system, so, too, can imitation sukuk or debt-based sukuk. Second, this paper is unique in exploring the ability of equity features to curb equityholders incentive to engage in risk shifting behaviour. Such an examination is necessary for the wake of the global financial crisis, for researchers and economists now agree that risk shifting must be controlled. 2018, Emerald Publishing Limited.